2002
DOI: 10.3732/ajb.89.9.1510
|View full text |Cite
|
Sign up to set email alerts
|

Monophyly of the Convolvulaceae and circumscription of their major lineages based on DNA sequences of multiple chloroplast loci

Abstract: Convolvulaceae, a large family of worldwide distribution, exhibit a rich diversity of morphological characteristics and ecological habitats. Previous efforts to systematize this diversity without a cladistic phylogenetic framework have disagreed on the circumscription of the family as well as tribal composition and relationship. In order to circumscribe the family and assess the relationships among its major lineages, a broad data set was constructed containing representatives of all ten recognized tribes of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
147
0
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 68 publications
15
147
0
18
Order By: Relevance
“…The Gondwanian origins of the two tribes, however, were postulated by some authors because most basal extant taxa of Solanaceae occur in the southern hemisphere (Hoare and Knapp, 1997;Symon, 1991;Tu et al, 2005;Ungricht et al, 1998). Based on the molecular phylogeny of Solanaceae and Solanales (Bremer et al, 2002;Olmstead et al, 2008;Stefanovic et al, 2002) and their overall distributions, Olmstead et al (2008) suggested the New World as the most likely place of origin for the family with eight to nine minimum dispersal events into the Old World, which include the dispersals of Mandragoreae and Hyoscyameae.…”
Section: Introductionmentioning
confidence: 99%
“…The Gondwanian origins of the two tribes, however, were postulated by some authors because most basal extant taxa of Solanaceae occur in the southern hemisphere (Hoare and Knapp, 1997;Symon, 1991;Tu et al, 2005;Ungricht et al, 1998). Based on the molecular phylogeny of Solanaceae and Solanales (Bremer et al, 2002;Olmstead et al, 2008;Stefanovic et al, 2002) and their overall distributions, Olmstead et al (2008) suggested the New World as the most likely place of origin for the family with eight to nine minimum dispersal events into the Old World, which include the dispersals of Mandragoreae and Hyoscyameae.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Miller et al (2002) made a comparison of Bayesian and maximum likelihood techniques. Each of these studies found somewhat different results, from no resolution (Stefanovic et al 2002) to alliance with different arrays of species (Manos et al 2001, Miller et al 1999. Some studies suggested an alliance of I. aquatica with section Mina, but Miller et al (2004) excluded it, without comment, from further study of that group.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Other sequences used to examine relationships within Ipomoea were waxy (Manos et al 2001, Miller et al 1999, and the four chloroplast regions rbcL, atpB, psbE-J operon, and the trnL-trnF intron/spacer (Stefanovic et al 2002). In addition, Miller et al (2002) made a comparison of Bayesian and maximum likelihood techniques.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…Así, tomando en cuenta que la derivación de láminas simples a láminas compuestas puede apreciarse como una homología dentro de las dicotiledóneas (Bharathan & Sinha 2001;Champagne & Sinha 2004) parece plausible considerar que el patrón actinódromo, compartido con las tribus basales de la familia Convolvulaceae (Stefanovic et al 2002) es el estado más ancestral de la venación en Merremia, y que mediante cuatro eventos diferentes pudieron desarrollarse todos los patrones de venación actualmente observados.…”
Section: Morfología Foliarunclassified